Hormone replacement therapy 11 years after WHI: when and what benefits to expect? - Bińkowska, Małgorzata; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
A decade after the presentation of the first results of the WHI study, medical experts are still discussing the interpretation of detailed results and the balance between the benefits and risks of hormone replacement therapy (HRT) in women after the menopause. There is a consensus that systemic HRT for relatively healthy women up to the age of 59 and/or within 10 years of the menopause is the best treatment of vasomotor symptoms, improves quality of life and does not increase the risk of coronary heart disease. There is no doubt that HRT requires an individual approach. The decision on the type of therapy, the route of administration and the dose of estrogen, should be based on the assessment of all menopausal symptoms, priorities of the woman, her age, time since the menopause, risk factors for cardiovascular diseases and risk of breast cancer. Regarding the differences between both arms of the WHI study it is accepted that the only purpose of concomitant progestagen is to protect endometrium in women with an intact uterus. The risk of venous thromboembolism and ischemic stroke is low, it depends on the route of administration, the age and body mass index. The risk of breast cancer increases after 5 years of estrogen-progestagen therapy, but in the case of estrogen alone there is no increase after 7 years of therapy. Studies on the understanding of that phenomenon are continued. Local administration of estrogen is a safe and effective treatment of symptoms of genitourinary atrophy, independent of the woman’s age. A new updated recommendation about HRT use should be a result of reanalysis of all the data and this essential discussion.